Comparative Evaluation Of Intrathecal Fentanyl And Midazolam As An Adjuvant With Hyperbaric Bupivacaine In Caesarean Section (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background  The study was done to compare and evaluate the effects of intrathecal fentanyl and midazolam as an adjuvant with hyperbaric bupivacaine. Material and Methods This study was conducted on 90 adult female patients aged 18-35 years and ASA grade I/II  undergoing elective or emergency caesarean section. The patients were randomly divided into  three groups having 30 patients in each group. Group A received 1.5ml 0.5% Bupivacaine plus  0.5ml NS, Group B received 1.5ml 0.5% Bupivacaine with 0.5ml (25 mcg) Fentanyl, Group C  received 1.5ml 0.5% Bupivacaine with 0.5ml (2.5 mg) Midazolam. Results  There was no significant difference in the demographic data and surgical characteristics in the  three groups. Regression to sensory level S2 was significantly prolonged in Group B  (257.87±11.95 min) and Group C(252.87±8.66min) as compared to Group A(151.80±8.0min).  However, the duration of motor blockade was comparable between Group A, Group B and  Group C (P value>0.05). Duration of complete and effective analgesia was significantly  prolonged in the Group B and Group C as compared to Group A (p
Keywords: Intrathecal Fentanyl; Midazolam; Hyperbaric Bupivacaine; Caesarean